The Disintegration of The Nation from Ethnocentrism, Cultural Acculturation, Mass Media, and New Media - Lani, Oktri Permata; Aris, Sarmen; Sulastri, Irta (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
Awareness of the importance of harmony between religions, ethnicities, races, and cultures must always be realized through an understanding of national integration. One of the barriers to this is ethnocentrism, cultural acculturation, and the media, both mass media and new media. Indonesia is one of the countries that are prone to experiencing resistance as a result of excessive fanaticism so if this is allowed to pass, it will have an impact on the integrity of the nation so that national disintegration can emerge. This is what we try to analyze in this paper, the problem of national disintegration is studied through three reviews, namely ethnocentrism, cultural acculturation, and the role of the mass media. The method used in writing this article is a qualitative approach, related to subjective social reality and uses non-participant observation or refers to literature studies. When we talk about ethnocentrism, of course, it is indirectly related to the interactions that are carried out by one person to another individual, individual to the group, or group to group. This interaction can occur with the help of communication. Whatever the form and context of communication, it always displays climate differences between communicators and communicants. Ethnocentrism is widely positioned as oil or fire that can devour people and objects around it. Likewise, ethnocentrism can be a trigger for disharmony and continuous conflict because when interacting both personally with personal, personal with groups and groups against other groups, they always understand and appreciate the superiority of their culture over other cultures. Ethnocentrism is the habit of each group to regard the culture of their group as the best culture.